The Role of Labor Market Institutions in the Impact of Immigration on Wages and Employment - Mette Foged; Linea Hasager; Vasil Yasenov (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
We study the role of institutions in affecting the labor market impacts of immigration using a cross-country meta-analysis approach. To accomplish this, we gather information on 1,030 previously estimated wage effects and 432 employment effects of immigration from 61 academic studies covering 18 developed countries. The mean and median impact on the relative wage of directly exposed native workers are negative and significantly different from the small positive mean and median impact on the average wage level. This pattern is reversed for employment effects where the magnitudes are smaller. We combine this database with country-level data on labor market institutions from the OECD. The results suggest that institutions may shield native workers from distributional (relative) wage consequences of immigration but exacerbate the impacts on average wages in the economy. We do not detect a significant and robust association for the employment effects of foreign workers.
Keywords: D02; J08; J15; J31; J61; 330; immigration; wages; employment; labor market institutions; meta-analysis